1994
DOI: 10.1111/j.1439-0523.1994.tb00696.x
|View full text |Cite
|
Sign up to set email alerts
|

Interspecific Crossability and Inheritance in Pelargonium

Abstract: 1 )ittci'ciit Pelargonium liyliriiis .vc of grcu inipoit,iTicc HI luirticulturo. Brooding lor I', liybrid .ind clon.il cultiv,irs IS p,irnciil,irly prcv,ilcm in I'.uropo, .l,ipAn .md North AriK'rio,\. Tlio results of ,i gre,tt de,>l of breeding rese,ueli ,ire sotterod tlirotigln>ut ditforont |otirn,ils .ind pulilished ni sevor,il diltorent Kingti.iges. I lie ,iini ot this review is to sumni,iri/e the results ot rese,irLh on mterspeeifle erosses and the inherit,\nee ot tlower ,ind le,it colour, pKiiit h,tbit, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 36 publications
(4 reference statements)
0
15
0
Order By: Relevance
“…Another group, P. peltatum hybrids, are called the ivy leafed geraniums. Among flowering plants, geraniums command a substantial portion of the market share (Horn, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Another group, P. peltatum hybrids, are called the ivy leafed geraniums. Among flowering plants, geraniums command a substantial portion of the market share (Horn, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Examples can be found in pot azaleas (Heursel and Horn, 1977), Primula (Horn and Eltorkey, 1989), Pelargonium (Horn, 1994), Gerbera (Tyrach and Horn, 1997), and cyclamens (Takamura eta/., 2000). There are numerous examples in floriculture crops where genes for certain flavonols or anthocyanins can be defined in terms of the biosynthetic pathway by analogy.…”
Section: Inheritance Of Flower Colormentioning
confidence: 99%
“…The designated lectotype for the genus Pelargonium is the hoodedleaf pelargonium (van der Walt and Vorster, 1981). In a review of interspecific crossability in Pelargonium, Horn (1994) reported that species in the section Pelargonium were crossed with species in Polyactium, Hoarea, and Glaucophyllum resulting in viable seeds.…”
Section: Geneticsmentioning
confidence: 99%